A review on water governance in Sri Lanka: the lessons learnt for future water policy formulation - S. S. K. Chandrasekara (IWA Publishing, 2021)
Sri Lanka has no water scarcity within the country, and per capita, water availability is adequate to cater for the country's estimated peak population. Nevertheless, the frequent variability of spatial and temporal water availability and extreme events have built up a water scarcity in Sri Lanka, which has been observed during the last two to three decades. Therefore, effective and efficient water governance is most important in today's context, and regular review and amendment of policies, laws, and regulations are crucial to mitigate water scarcity. Although a few attempts were initiated, none of them succeeded. In this study, historical and present water governance mechanisms, including coordinating mechanisms and implementing water management agencies in Sri Lanka, were comprehensively reviewed. Further, the previously proposed water policies, their status and reasons for the failures of policies were discussed. Finally, the formulation of a novel institutional arrangement or altering the existing institutional arrangement with shared data and allocating non-shared responsibilities to each institution is suggested for better water governance in Sri Lanka. Highlights Monarchs guided by the Buddhist monasteries governed ancient WRM in Sri Lanka.; Water Management Panel under the jurisdiction of Mahaweli Authority coordinates WRM.; Donor organizations proposed economic value to irrigation water.; Concept of privatizing the irrigation water hindered the acceptance of the water policy.;